Theory and Practice in Dividend Distribution - Buchanan, Norman S. (Quarterly Journal of Economics, 1938)
I. Application of marginal principle to dividend distribution, 64.— Case of the small expanding corporation, 68.— The cash position, 69.— II. Statistical investigation of the problem presents many difficulties, 70.— Individual corporations over long period, 71.— Income tax data, 72.— Fraction of net incomes customarily ploughed back, 73.— III. Principles of dividend distribution which appear to have guided corporate directorates: the cash position, 78; fear of illegality, 78; accumulation of surplus against possible future losses, 78; stabilization of dividend rates, 79; special interests of management groups, 81; custom, 83.— IV. Conclusions, 84.